2012
DOI: 10.1111/j.1541-0064.2012.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in vulnerability of crop production to drought in southern Alberta

Abstract: Growing evidence of global climate change has led to global concerns over the vulnerability of agriculture to drought. Located in a semiarid environment, southern Alberta has suffered significant losses of agricultural productivity due to drought hazards in recent decades. Understanding the relationship between crop production and drought conditions is essential for coping with increasingly uncertain climate conditions. This study attempts to quantify the magnitude of crop production vulnerability to drought i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Observed adaptation responses in Mediterranean environmental zones by introducing new and more suitable cultivars were documented Meza et al 2008 Evaluate the impacts of climate change scenarios on the productivity of two maize cultivars in central Chile using Ceres Maize in DSSAT v 4.0. They evaluate the possibility of double cropping as a response to changes in the length of the growing season Xu et al 2012 Explain the observed patterns of vulnerabilities also in terms of different adaptive capacities in a semiarid area of southern Alberta. They quantitatively assess the vulnerability of an agricultural system by coupling the agricultural yields with the climatic stressors…”
Section: Introduction: Impacts Stressors Vulnerability and Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…Observed adaptation responses in Mediterranean environmental zones by introducing new and more suitable cultivars were documented Meza et al 2008 Evaluate the impacts of climate change scenarios on the productivity of two maize cultivars in central Chile using Ceres Maize in DSSAT v 4.0. They evaluate the possibility of double cropping as a response to changes in the length of the growing season Xu et al 2012 Explain the observed patterns of vulnerabilities also in terms of different adaptive capacities in a semiarid area of southern Alberta. They quantitatively assess the vulnerability of an agricultural system by coupling the agricultural yields with the climatic stressors…”
Section: Introduction: Impacts Stressors Vulnerability and Adaptationmentioning
confidence: 99%
“…There are significant conceptual and methodological differences in the studies summarized in Table 1. However, Xu et al (2012) defined vulnerability as having three elements: exposure (to climate stress), sensitivity, and adaptive capacity. Ventrella et al (2012) specifically evaluated the potential of irrigation and fertilization toward the mitigation of climate impacts.…”
Section: Introduction: Impacts Stressors Vulnerability and Adaptationmentioning
confidence: 99%
“…Qualitative approaches (16% of all articles) were also used by incorporating stakeholder knowledge and opinions through interviews (Disch et al, 2012; Hurlbert & Montana, 2015), surveys (e.g., Kruse & Seidl, 2013; Olesen et al, 2011), workshops (Hill et al, 2014; Kruse & Seidl, 2013), or focus groups (McMartin et al, 2018). Five articles looked at vulnerability in connection to impact analyses using other approaches than simulation models (Bosela, Stefancik, et al, 2021; Bosela, Tumajer, et al, 2021; Buras et al, 2018; Erfurt et al, 2019; Xu et al, 2012).…”
Section: Synthesis Of Relevant Drought Studiesmentioning
confidence: 99%
“…The third most commonly used vulnerability factor in the reviewed literature was exposure to drought (Figure 5), repeatedly measured using drought hazard indices such as the Standardized Precipitation Index (Popova et al, 2014; Xu et al, 2012), Standardized Groundwater Drought Index (Minea et al, 2020), the Palfai Drought Index (Buzasi, 2021; Buzasi et al, 2021), and the Climate Moisture Index for forest vulnerability (e.g., Aubin et al, 2018; Brecka et al, 2020).…”
Section: Synthesis Of Relevant Drought Studiesmentioning
confidence: 99%
“…Temperature stress can cause plants to go through morphological and biochemical changes in order to adapt to adverse conditions (Moretti et al, 2010;Qaderi et al, 2012;Xu et al, 2012;Prasch and Sonnewald, 2015;Martel and Qaderi, 2016;Abo Gamar et al, 2019. DaMatta et al (2010) stated that, in regions of low latitude, a modest increase of 1-2 o C would have negative impacts on the yield of crops.…”
Section: Introductionmentioning
confidence: 99%